The influence of age and nutrients on insulin sensitivity - Chee, Carolyn (2016)
The studies presented in this thesis aimed to investigate the effects of nutritional modulation and age-associated changes on insulin sensitivity. Four separate studies were performed; three of these had insulin sensitivity as the primary outcome. Existing studies show that ageing is associated with insulin resistance, but data may be confounded by several factors that also occur with increasing age, such as increased adiposity, skeletal muscle lipid accumulation and reduced physical activity. To elucidate this further the first study compared body composition, skeletal muscle lipid content, fat metabolism during light-intensity exercise and whole-body and skeletal muscle insulin sensitivity between 7 healthy young and 14 older males. Ageing and insulin resistance are also associated with impaired skeletal muscle protein synthesis, however the effects of insulin resistance per se on amino acid metabolism and associated insulin signalling pathways are not really known. The second study involved 8 young healthy males and aimed to explore the effect of insulin resistance on the protein synthetic response to amino acid ingestion and muscle protein signalling pathway in humans. Dietary intake has been shown to affect insulin sensitivity; however it is unclear if diet composition affects liver fat content independent of energy balance. Therefore the third study aimed to investigate the effects of hyperenergetic diets high in fat or carbohydrate on liver fat and insulin sensitivity. The study involved 23 healthy but overweight and obese males who initially consumed an isoenergetic diet for one week, and then were randomised to 2 weeks of either hyperenergetic (+25% excess) high fat or high carbohydrate diets. Liver fat content, abdominal visceral fat, skeletal muscle fat content, hepatic lipid metabolism and insulin sensitivity were assessed before and after the 2 week intervention period. Whilst dietary excess can exacerbate insulin resistance, certain micronutrients may improve insulin sensitivity. Carnitine has shown encouraging outcomes in relation to promoting fatty acid oxidation, metabolism and modulating body composition in healthy young volunteers. However the effects on older people have never been explored. This formed the basis of the fourth study that investigated the effects of 6 months of oral carnitine supplementation or placebo in 14 older (≥65 years of age) healthy males in relation to fatty acid metabolism, skeletal muscle lipid and insulin sensitivity. The main findings are summarised. Irrespective of age, adiposity and physical activity are associated with impaired fatty acid oxidation, greater skeletal muscle lipid accumulation and reduced insulin sensitivity. However ageing per se appears to increase the sympathetic response to exercise and enhance systemic fatty acid delivery and adipose tissue lipolysis. Insulin resistance induced by acute elevation of lipid was found to affect the skeletal muscle protein synthetic response to amino acid ingestion, and this impairment appeared to occur downstream from the Akt insulin signalling pathway. Energy excess per se increases liver fat content and affects liver metabolism but there were no differential effects of carbohydrate or fat on hepatic insulin sensitivity and liver fat content. Finally, oral carnitine ingestion for 6 months successfully increased skeletal muscle total carnitine content of older healthy people and resulted in increased fatty acid oxidation and intramyocellular lipid (IMCL) utilisation during light-intensity exercise, but no effect on skeletal muscle insulin sensitivity was seen. These studies have increased mechanistic insight into the associations between ageing, nutrients and insulin sensitivity, paving the way to further research.